The role of political competition in the link between electoral systems and corruption: an extension - Maria Rosaria Alfano; Anna Laura Baraldi (European Journal of Government and Economics (EJGE), 2015)
This work provides an extension to an international context of the analysis made by Alfano, Baraldi and Cantabene (2013) on the role of political competition as a channel through which electoral systems affect corruption. Our result conflicts with that found by empirical literature on that topic that makes plurality rules the most virtuous in terms of corruption. Political scientists must be cautious in designing the degree of proportionality of electoral rules without take into account the variation in political competition that follows.
Keywords: 330; Political competition; electoral systems; corruption.